Structural Damage Detection Based on Modal Parameters Using Continuous Ant Colony Optimization - Aditi Majumdar; Bharadwaj Nanda; Dipak Kumar Maiti; Damodar Maity (Advances in Civil Engineering)
A method is presented to detect and quantify structural damages from changes in modal parameters (such as natural frequencies and mode shapes). An inverse problem is formulated to minimize the objective function, defined in terms of discrepancy between the vibration data identified by modal testing and those computed from analytical model, which then solved to locate and assess the structural damage using continuous ant colony optimization algorithm. The damage is formulated as stiffness reduction factor. The study indicates potentiality of the developed code to solve a wide range of inverse identification problems.